Długookresowe zmiany roślinności w zespole sosnowego boru bagiennego Vaccinio uliginosi-Pinetum Kleist 1929 - Czerepko, Janusz (Leśne Prace Badawcze, 2011)
Marshy pine forests have a relatively broad range of distribution across Europe but are very scattered. The typical Vaccinio uliginosi-Pinetum association is mainly restricted to nature reserves, because bog forests have been drained in many unmanaged sites where they naturally occur. Changes in the vegetation of natural forest associations in protected areas of NE Poland were studied with respect to environmental changes and ongoing autogenic successional processes in Vaccinio uliginosi-Pinetum associated plant communities. Changes in the species composition of natural communities after ca. 40 years were monitored on 14 relevés in nature reserves. Most plots (nine) were located in the Białowieża National Park with the rest in nature reserves in the Augustów and Knyszyn forests. The re-sampling of phytosociological relevés was done by the same method originally used by Braun- Blanquet. The groundwater table and depth of organic layer were measured close to each relevé edge. The collection of vegetation data for the two periods (old – new relevés) included such parameters as: species richness, cover of layers, ecological indicator values, number of occurrences and cover coefficients of species and particular taxonomical groups. The analysis of vegetation changes in natural communities of marshy pine forest indicated that four more species were present than in the past. The largest changes in species richness occurred in the moss and herbaceous flora. The mean number of trees, shrubs and herbaceous species per plot increased significantly. Notable changes in the vertical structure of forest communities were visible. There was also an increase of ca. 20% in the secondary layer of tree canopy cover and a concomitant decrease in the moss layer. The depth of the soil organic layer reached 150 cm. The groundwater table exhibited large seasonal fluctuations in height between spring (mean of 24.3 cm) and summer (mean of 86 cm). There were changes in all the measured parameters describing the species composition of the Vaccinio uliginosi-Pinetum association. Tree species Picea abies , Betula spp. and Quercus robur , all increased in abundance over the period between sampling and re-sampling, either through increased presence in the lowest layer of stands in new relevés or, in the case of Quercus robur , previously unreported occurence in the shrub layer. Many species characteristic of bog communities disappeared or significantly decreased in abundance, whereas some species typical of mineral soils became more common. The vegetation in repeatedly sampled plots became more chacteristic of wet sites than the initial bog sites over the 40 year period between sampling.